If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3x + -2) = -3x + 7 Reorder the terms: -2(-2 + 3x) = -3x + 7 (-2 * -2 + 3x * -2) = -3x + 7 (4 + -6x) = -3x + 7 Reorder the terms: 4 + -6x = 7 + -3x Solving 4 + -6x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + -6x + 3x = 7 + -3x + 3x Combine like terms: -6x + 3x = -3x 4 + -3x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + -3x = 7 + 0 4 + -3x = 7 Add '-4' to each side of the equation. 4 + -4 + -3x = 7 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 7 + -4 -3x = 7 + -4 Combine like terms: 7 + -4 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| 9x^2+6x=-2 | | 1/3x+7=12 | | 2x+36-2y+x+y=180 | | 2x+36-2y+x+7=180 | | 1/w-1-1/5w-5=4/5w-5 | | (4h-3)-(2h-8)= | | 33-7(n)=9075 | | y=220x^2+25x | | -4+10x-4x^2=0 | | 18069333.33333=(1/3)(440^2*x) | | 5x-12=16-12x | | (x-5)(x-6)=x^2+3x+7 | | 4(n-4)=1+5n | | y-4=6(x-6) | | x(a-b)-x(a+b)+4b^2=0 | | 63-7x=2x+16 | | 4w+3=-7 | | 4w+3=7 | | y=6-3 | | 2t-3=-3t+2 | | x*x+14=1887 | | -2(2x-5)=-3+7-x+3 | | 9x^2-54x-1=0 | | x+(x-30.2)+(x+25.7)=197.1 | | 3x^2-2kx-k+8=0 | | x+5=-3x+7 | | 1+1=x^2 | | (M-4)(m-6)(m-3)/(m-2)(m-12)(2m-3) | | 1x+1/3x=8 | | If+3I=2f+4 | | 5e/2=-2 | | 1/3/4 |